Occurrence of Multi-Drug-Resistant Escherichia coli in Chickens, Humans, Rodents and Household Soil in Karatu, Northern Tanzania - Valery S. Sonola; Abdul S. Katakweba; Gerald Misinzo; Mecky I. N. Matee (MDPI AG, 2021)
We investigated antibiotic resistance profiles of Escherichia coli among 960 samples obtained from chickens (236), humans (243), rodents (101) and soil (290). E. coli was isolated from 650 (67.7%) samples. Isolation frequency varied significantly between chickens, humans, rodents and soil samples, being 81.6%, 86.5%, 79.2% and 31.0%, respectively (p < 0.001). Resistance rates were particularly higher against imipenem (79.8%), cefotaxime (79.7%) and tetracycline (73.7%) and moderate against amoxicillin-clavulanate (49.4%). Overall, 78.8% of the isolates were multidrug-resistant (MDR) among which, 38.8%, 25.1%, 12.9% and 2.5% exhibited resistance to three, four, five and six different classes of antibiotics, respectively. Multidrug-resistant E. coli were observed in 27.7%, 30.3%, 10.8% and 10.0% of the isolates from chickens, humans, rodents and soil samples, respectively. Our results show high levels of antimicrobial resistance including MDR in E. coli isolated from chickens, humans, rodents and soil samples in Karatu, Northern Tanzania. Comprehensive interventions using a one-health approach are needed and should include improving (i) awareness of the community on judicious use of antimicrobial agents in humans and animals, (ii) house conditions and waste management and (iii) rodent control measures.